The Relationship between the Implementation of Digital Transformation Requirements and the Quality of E-learning: A Field Study - Ahmed, Mahmoud Samah Ahmed; Abdelaziz, Amira Ahmed Mohamed (The Arab Journal of Administration, 2024)
The study aimed to: study the relationship between implementing the requirements of digital transformation, which is (spreading the culture of digital transformation, designing electronic programs and courses, human requirements, technical requirements) and the quality of e-learning, which is (quality of the e-learning system, quality of e-learning management, quality of content for learning courses, the quality of the faculty member’s use of the system, the quality of student support), and to identify whether there is a difference in the degree of availability of digital transformation requirements, and the quality of e-learning from the point of view of the faculty members and their assistants and the point of view of the students in the colleges under study. Study Methodology: The study was designed to rely on the descriptive analytical approach to study the relationships between variables. Population and study sample: The study population is the colleges of commerce and engineering located in the Egyptian public universities in the Greater Cairo region (10 colleges). Two samples were drawn: the first from faculty members and their assistants (357) individuals, and the second from students (420) individuals. The study found: There is a significant relationship with statistical significance between the implementation of digital transformation requirements and the quality of e-learning in the colleges under study from the point of view of faculty members and their assistants, as well as from the point of view of students. It also found that there are no fundamental differences with moral significance between the opinions of faculty members and their assistants. And the opinions of students regarding the requirements of digital transformation, while significant differences were found between the opinions of the two samples regarding the quality of e-learning.